2007
DOI: 10.1111/j.1471-4159.2007.04777.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminoindan and hydroxyaminoindan, metabolites of rasagiline and ladostigil, respectively, exert neuroprotective properties in vitro

Abstract: The anti-Parkinson, selective irreversible monoamine oxidase B inhibitor drug, rasagiline (Azilect), recently approved by the US Food and Drug Administration, has been shown to possess neuroprotective-neurorescue activities in in vitro and in vivo models. Recent preliminary studies indicated the potential neuroprotective effect of the major metabolite of rasagiline, 1-(R)-aminoindan. In the current study, the neuroprotective properties of 1-(R)-aminoindan were assessed employing a cytotoxic model of human neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Both are believed to act by inhibition of monoamine oxidase B (MAO B). However, both are metabolized in a different way: rasagiline gives rise to aminoindan, a compound reported to have neuroprotective capabilities of its own, whereas selegiline gives rise to the neurotoxic metabolite methamphetamine [1,2]. Similar electropharmacograms obtained by quantitative brain field potential analysis were obtained from freely moving rats in the presence of rasagiline and its metabolite aminoindan (not inhibiting monoamine oxidase B).…”
Section: Introductionmentioning
confidence: 91%
“…Both are believed to act by inhibition of monoamine oxidase B (MAO B). However, both are metabolized in a different way: rasagiline gives rise to aminoindan, a compound reported to have neuroprotective capabilities of its own, whereas selegiline gives rise to the neurotoxic metabolite methamphetamine [1,2]. Similar electropharmacograms obtained by quantitative brain field potential analysis were obtained from freely moving rats in the presence of rasagiline and its metabolite aminoindan (not inhibiting monoamine oxidase B).…”
Section: Introductionmentioning
confidence: 91%
“…Preservation of Cx43 phosphorylation by selective activation of the ɛPKC isoform occurs in response to ischemic pre- [11,34,60] and postconditioning [39,40,61], in which brief episodes of ischemia reduce the adverse effects of subsequent or preceding myocardial ischemia, respectively. PKC isoform-selective modulator drugs are currently under development for the treatment of a variety of diseases [3,10,48]. As the function of a multiple proteins may be affected by such drugs, delineation of the isoform-specific regulation of downstream targets, e.g., Cx43Hc, is important to improve our understanding of the pathogenesis of ischemic heart disease and to identify new opportunities for drug development.…”
Section: Perspectivementioning
confidence: 99%
“…209 Recent studies have demonstrated that the rasagiline metabolite aminoindan exerts protective effects that might also contribute to the benefits provided by rasagiline. 210 To test for a possible neuroprotective effect in patients with PD, a novel study design, the "delayed start," was used in an attempt to avoid the confounding symptomatic effects seen with other clinical trial designs 211 (figure 8). The delayed-start study is conducted in two stages.…”
Section: Apoptosismentioning
confidence: 99%